Extracción asistida por ultrasonido de compuestos fenólicos y capacidad antioxidante de residuos del café (café silverskin) variedad arábica (Coffea arábica L.) - Olano Quiñones, Magali Yanises (2019)
Coffee is one of the most consumed beverages worldwide, so the coffee industry, coffee shops and restaurants are constantly growing. Consequently, large amounts of solid coffee silverskin (CS) waste are generated. The CS is a fine tegument, which is obtained through the roasting process. This residue can be reused due to its bioactive compounds. The objective of the present study was to evaluate the effect of extraction time (T) (30-90 min), raw material / solvent ratio (MP / S) of (0.1 - 1 g / ml) and ethanol concentration (E ) (20-96%) on the ultrasound-assisted extraction (US) of total phenolic compounds (CFT) and antioxidant capacity (CA) of the CS Arabic variety. The response surface methodology was used through the central rotational composite design (DCCR), and a multi-response analysis was performed that simultaneously optimized both responses. The model predictions were correlated with a value of R = 90.26% for CFT and with an R = 99.27% for CA, with a strong in fl uence (p <0.05) of the variables (MP / S) and (E) in the results. The optimal conditions of (T) of 90 min, (MP / S) of 0.1 g / ml and (E) of 44.58% allowed to obtain a CFT content of 43.34 mg AG / 100g of CS and with a (T) of 30 min, (MP / S) of 1 g / ml and (E) of 89.92% allowed to determine a% inhibition of the DPPH radical of 72.40%. Likewise, the optimal conditions for the multi-response analysis were: (T) of 90 min, (MP / S) of 1 g / ml and one (E) of 53.99%; allowed to obtain a CFT content of 30.85mg AGE / 100g of CS and a% inhibition of DPPH radical of 54.86%. CS extracts could be useful as a good source of antioxidant materials.